ADAPTIVE SMART LEARNING MODEL: INOVASI PEMBELAJARAN DIGITAL BERBASIS KECERDASAN TEKNOLOGI DI MADRASAH IBTIDAIYAH - Bali, Muhammad Mushfi El Iq; Wulandari, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Study This aim implementing the Adaptive Smart Learning Model through the Quizizz platform to increase achievements cognitive, active, and motivational students in the eye Science lessons at MI Nurul Qodir. Focus mainly is evaluate effectiveness technology intelligent in transform material abstract